The Poetics of Heterogeneous Bodies in Contemporary Hungarian Literature - Nemeth, Zoltan (Porównania, 2022)
In contemporary Hungarian literature, an increasingly important role is played by post-humanist-anthropocene forms of literary expression, the starting point of which is biological operations performed on the body. The bodily transformations that change the anthropological and evolutionary picture of man are accompanied by new biological constructs and power relations, as a result of which animal life forms acquire hybrid identities. Three Hungarian novels are discussed in the work: My Hero’s Square (2000) by Lajos Parti Nagy, A patkány éve [Year of the Rat] (2013) by Imre Bartók, Irha és bőr [Hide and Skin] (2019) by Anita Moskát. Their analysis is set in the context of posthumanism, ecocriticism and postmodernism.